A Review of Open Research Data Policies and Practices in China. (29th January 2021) - Zhang, Lili; Downs, Robert R.; Li, Jianhui; Wen, Liangming; Li, Chengzan
This paper initially conducts a literature review and content analysis of the open research data policies in China. Next, a series of exemplars describe data practices to promote and enable the use of open research data, including open data practices in research programs, data repositories, data journals, and citizen science. Moreover, the top four driving forces are identified and analyzed along with their responsible guiding work. In addition, the "landscape of open research data ecology in China" is derived from the literature review and from observations of actual cases, where the interaction and mutual development of data policies, data programs, and data practices are recognized. Finally, future trends of research data practices within China and internationally are discussed. We hope the analysis provides perspective on current open data practices in China along with insight into the need for additional research on scientific data sharing and management.